Patossistema cucumis melo l.-podosphaera xanthii: variabilidade patogênica, identificação de fontes de resistência e estudo de herança - Ricarte, Anânkia de Oliveira (Universidade Federal Rural do Semi-Árido, 2019)
Among the diseases that occur in the melon, it is mentioned the powdery mildew, caused mainly by the fungal species Podosphaera xanthii. The use of genetic resistance is the most efficient way to avoid the pathogen. However, the high variability of the pathogen reduces the useful life of resistant cultivars, which makes it difficult to control the disease. Frequent surveys on the physiological races that are causing powdery mildew are necessary, as well as the identification of accesses that have resistance genes, with subsequent knowledge about the genetic control involved, in order to obtain cultivars resistant to the prevalent breeds of the pathogen. In view of the above, the objectives of this study were: a) To characterize the variability of P. xanthii population in melon producing regions in the State of Rio Grande do Norte; b) Identify resistant accessions of melon; c) To know the inheritance of the resistance present in the access AM-55 to the races 3.5 and 'Br06' of P. xanthii. Experiments were carried out in the period from 2015 to 2018, in which monosporic isolates from leaves infected with powdery mildew cultivated under field conditions and protected environment were analyzed. The isolates were inoculated in a set of differentiated lines of powdery mildew, and based on the resistance response or susceptibility presented by each of them it was possible to identify the breed of the isolates. Breeds 1, 2F, 3.5, 5, 'Br01', 'Br02', 'Br03', 'Br04', 'Br05' and 'Br06' were identified, with breeds 3.5 and 5 causing powdery mildew. This is the first record of the presence of race 3.5 in Brazil. In 2017, 47 accessions that were part of the active collection of germplasm of UFERSA were inoculated with three isolates of powdery mildew collected in the region of Pau Branco-RN, Alagoinha-RN and Baraúna-RN. Ten days after inoculation, the plants were evaluated and the data were analyzed according to the nonparametric Kruskal- Wallis test. It was observed the existence of variability among the genotypes, access AC-02, AC-32 and AC-59 were identified as resistant because they did not present colonization and reproduction of the pathogen. In the study of inheritance, the 'Védrantais' (susceptible) and AM- 55 (resistant) parents were used as well as the F1 and F2 populations, obtained from the crossbreeding between the parents. The plants were inoculated with isolates of the races 3.5 and 'Br06', as well as evaluated and classified based on a grading scale ranging from 1 to 4. Plants that received grades 1 or 2 were considered resistant, and plants with grades 3 or 4 were considered susceptible. The Chi-square test (χ2) was applied to the segregating population (F2) to test the possible genetic model and gene linkage through the analysis of the reaction in the F2 generation to both races simultaneously. The inheritance of resistance present in the AM-55 to the races 3.5 and 'Br06' of P. xanthii is monogenic and recessive. Genes that confer resistance to both races are linked, and the distance between them is 9cM
Keywords: Meloeiro; Oídio; Raças fisiológicas; Germoplasma; Monogênica recessiva; Melon; Powdery mildew; Physiological breeds; Germplasm; Monogenic recessive; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA